Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran Kooperatif Think Pair Share - Humaeroh Humaeroh; Muhamad Rais; Dwi Kartika Susanti (Journal on Education, 2024)
The ability of a teacher to modify the learning process will have a positive effect on improving student learning abilities. The purpose of this study is the application of the Think Pair Share cooperative learning approach to improve student learning outcomes on the Digestive System in Humans in Class VIII SMP Khas Putra Bangsa, Ciruas District, Serang Regency. This research uses Classroom Action Research (CAR). The number of respondents involved in this study 36 students. The data collection uses observation, questionare and test techniques. The data processing process applies descriptive qualitative. The results showed that the application off the Think Pair Share (TPS) cooperative model approach in learning about the digestive system in humans was suitable for class VIII students, because it wes able to encourage, motivate and develop student student learning creativity. From the results of observations in cycle I, cycle II and cycle III, learning outcomes continue to increase. This is evidence bt the acquisition of the average value of respondents’ learning outcomes from the precycle stage of 24, in the first cycle it increased to 46, in the second cycle it increased to 63, and in the third cycle it increased again by 78. The results showed that the cooperative learning model can encourage students to improve their learning outcomes.